Bilateral breast masses as a presentation for T-cell acute lymphoblastic leukaemia. Issue 8 (26th August 2020) - Mosalem, Osama; Abu Rous, Fawzi; Elshafie, Ahmed; Isaac, Daniel
Abstract : Here we describe a 27-year-old woman, 5 months post partum, who presented to the emergency department with bilateral breast masses. She was initially treated as lactational mastitis with no improvement. Breast ultrasound showed bilateral breast and axillary lymphadenopathy suggestive of metastatic/neoplastic process, and chest X-ray showed a large anterior mediastinal mass. Further work-up led to the diagnosis of T-cell acute lymphoblastic leukaemia. The patient was started on a paediatric regimen using the children's oncology group AALL0434 protocol. The patient achieved a complete remission following induction chemotherapy with resolution of her presenting symptoms.